Identification of NHLRC1 as a novel AKT activator from a lung cancer epigenome-wide association study (EWAS) - Faltus, Christian; Lahnsteiner, Angelika; Barrdahl, Myrto; Assenov, Yassen; Hüsing, Anika; Bogatyrova, Olga; Laplana, Marina; Johnson, Theron S.; Muley, Thomas; Meister, Michael; Warth, Arne; Thomas, Michael; et al. (International journal of molecular sciences, 2022)
Changes in DNA methylation identified by epigenome-wide association studies (EWAS) have been recently linked to increased lung cancer risk. However, the cellular effects of these differentially methylated positions (DMPs) are often unclear. Therefore, we investigated top differentially methylated positions identified from an EWAS study.
Gesehen am 15.11.2022